2010
DOI: 10.1208/s12249-010-9393-0
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan and Glyceryl Monooleate Nanostructures Containing Gemcitabine: Potential Delivery System for Pancreatic Cancer Treatment

Abstract: Abstract. The objectives of this study are to enhance cellular accumulation of gemcitabine with chitosan/ glyceryl monooleate (GMO) nanostructures, and to provide significant increase in cell death of human pancreatic cancer cells in vitro. The delivery system was prepared by a multiple emulsion solvent evaporation method. The nanostructure topography, size, and surface charge were determined by atomic force microscopy (AFM), and a zetameter. The cellular accumulation, cellular internalization and cytotoxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 41 publications
0
32
1
Order By: Relevance
“…There was no significant (p<0.05) difference observed in the particle size of drug-loaded GMOchitosan and PLGA nanoparticles. In contrast to the previous studies with GMO-chitosan nanoparticles in our lab (20,21), the present study produced particles of smaller size. The Values are mean±SD; n=3 n/d not defined, PTX paclitaxel, CYP cyclopamine, EE entrapment efficiency difference could possibly be attributed to the use of poloxamer as a stabilizer instead of PVA.…”
Section: Nanoparticle Characterizationcontrasting
confidence: 96%
See 2 more Smart Citations
“…There was no significant (p<0.05) difference observed in the particle size of drug-loaded GMOchitosan and PLGA nanoparticles. In contrast to the previous studies with GMO-chitosan nanoparticles in our lab (20,21), the present study produced particles of smaller size. The Values are mean±SD; n=3 n/d not defined, PTX paclitaxel, CYP cyclopamine, EE entrapment efficiency difference could possibly be attributed to the use of poloxamer as a stabilizer instead of PVA.…”
Section: Nanoparticle Characterizationcontrasting
confidence: 96%
“…Our laboratory was previously involved in the development of GMO-chitosan nanoparticles for the delivery of hydrophilic as well as hydrophobic anticancer agents utilizing the bioadhesive properties of chitosan and GMO for targeting the cancer tissue (20,21). However, in the previous studies, we have only reported the targeting of drugs individually and not in combination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan has the higher degree of deacetylation, which makes it more soluble in biological system (Sannan et al 1976). The low-molecular-weight chitosan also helps to achieve smaller particle size and better redispersibiliy of particles in water (Trickler et al 2010). The nanoparticles prepared with chitosan produce positive surface charge.…”
Section: Stability Of Ifosfamide Loaded Nanostructured Lipid Carriermentioning
confidence: 99%
“…The preparation method developed by Trickler et al was used for the preparation of GMO-chitosan nanoparticles (15). In brief, 1.75 ml of GMO was melted and added to 12.5 ml of 1% w/v poloxamer 407 solution.…”
Section: Preparation Of Gmo-chitosan Nanoparticlesmentioning
confidence: 99%